Employees' effort-reward imbalance in the banking industry – a discussion paper. (1st January 2012) - Nolte, Andreas; Stummer, Harald
During the last years, the banking industry has faced several challenges and crises leading to the closure of banks, the foundation of bad banks or to temporary nationalisation of banks. While in the USA or in Japan, investment and commercial banks are separated from each other, in Continental Europe, especially in Germany and Austria, universal banks are the rule. Here, the losses produced in investment banking generally influence also the traditional saving and loans business directly. Employees in the saving and loans business face increasing pressure due to general risk adjustments or the external risk seen by the markets, or just due to changing governance structures in the service sector. The present paper discusses the health effects on employees in the banking industry using own and secondary empirical data. Especially employees with direct customer contact face higher imbalances between effort and reward and show negative health effects.